Evolutionary complications of two anterior tibial artery injuries - Piñeyro, Alberto; Olivera, Daniel; Carriquiry, Luis; Rodríguez, José L.; Luksenburg, Jaime (Cirugía del Uruguay, 1982)
Two injuries of the anterior tibial artery, totally unnoticed at the begining, are presented. As a developing complication, one of the injuries, developed a Pseudoaneurysm and the other one, en arteriovenous fistula. A brief review is made on the subject.